Comparison of properties of natural rubber compounds with various fillers - Kamal Mazlina Mustafa; Clarke Jane; Md Aris Ahmad (Journal of Rubber Research, 2009)
DL
Keywords: Calcium carbonate; Carbon black; Reinforcement; Silica clays; Starch; Strength